2018
DOI: 10.5296/jmr.v10i3.13253
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intentions of Pakistani Students: The Role of Entrepreneurial Education, Creativity Disposition, Invention Passion & Passion for Founding

Abstract: The purpose of this study was to investigate the impact of entrepreneurial education on entrepreneurial intentions of the university students, moreover, a mediating role of  Entrepreneurial Passion, Perceived Creativity Disposition and Entrepreneurial Passion was also assessed. Data were collected from 595 university students; Partial least square technique was used with the help of SmartPLS software. Results of partial least square structural equation modeling showed that all the hypothesized direct and indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 64 publications
1
39
1
3
Order By: Relevance
“…It means that passion was the key element affected by the entrepreneurship intention was examined by academic and non-academic. This research finding supported the results from Cardon et al (2009) and Anjum et al (2018) as passion is a motivation element to human being's behavior. The main result of this study once again confirmed the mediating role of the passion between identity centrality and entrepreneurship intention in Vietnam context.…”
Section: Discussionsupporting
confidence: 87%
“…It means that passion was the key element affected by the entrepreneurship intention was examined by academic and non-academic. This research finding supported the results from Cardon et al (2009) and Anjum et al (2018) as passion is a motivation element to human being's behavior. The main result of this study once again confirmed the mediating role of the passion between identity centrality and entrepreneurship intention in Vietnam context.…”
Section: Discussionsupporting
confidence: 87%
“…Individuals with a high level of enthusiasm or passion are more inclined to become entrepreneurs. Anjum et al (2018) found a positive and significant relationship between creativity and entrepreneurial passion. Moreover, scholars indicate that a higher level of entrepreneurial passion in a person is more creative in his or her performance to accomplish a task.…”
Section: Creativity and Entrepreneurial Passionmentioning
confidence: 88%
“…For entrepreneurial passion, the measurement scale of Anjum et al (2018) was adopted, and the scale was translated. Among them, the entrepreneurial passion contains 14 items, the HP and the obsessive passion each contain 7 items.…”
Section: Methodsmentioning
confidence: 99%